1986
DOI: 10.1063/1.451779
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on polyaniline

Abstract: Theoretical predictions for various neutral and charged forms of polyaniline are presented and discussed. The MNDO semiempirical method is used to predict geometries which serve as input for valence effective Hamiltonian (VEH) calculations of the electronic band structure. The VEH calculations provide predictions for the band gaps, ionization potentials, electron affinities, and redox potentials for the various forms of polyaniline. Where possible, comparison is made to experiment with generally favorable resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(52 citation statements)
references
References 26 publications
4
47
1
Order By: Relevance
“…In Table 1, we present the heats of formation of these compounds obtained by full optimization of the geometric structures. The benzoid form of the PAn dimer is more stable in the gas phase than the quinoid-benzoid form, as previously reported [ 15,18,19]. Pyrrole dimers can be obtained by various linkages between (Y and p carbons.…”
Section: Calculations and Discussionsupporting
confidence: 56%
“…In Table 1, we present the heats of formation of these compounds obtained by full optimization of the geometric structures. The benzoid form of the PAn dimer is more stable in the gas phase than the quinoid-benzoid form, as previously reported [ 15,18,19]. Pyrrole dimers can be obtained by various linkages between (Y and p carbons.…”
Section: Calculations and Discussionsupporting
confidence: 56%
“…As highlighted in Figure 2, our molecular engineering approach to the central p-conjugated units in the rest of the series now allows for large and tunable modifications of the electronic structure of the different TANIs, resulting in bathochromic shifts of up to 24 nm and hypsochromic shifts of up to 90 nm for the first and second transitions, respectively. For 1EB and 2EB the two absorption maxima (l 1max and l 2max ) have previously been assigned to p-p* and n-p* transitions, respectively, based on theoretical [30,31] and experimental [32][33][34] studies of polyA C H T U N G T R E N N U N G (aniline) (PANI). However, more recent work [35] on oligoA C H T U N G T R E N N U N G (aniline)s suggested that l 2max is actually a further p-p* transition.…”
Section: Resultsmentioning
confidence: 99%
“…5 together with the results of a Huckel calculation for the electronic band structure of LEB carried out assuming that the repeat unit is a single (C 6 H 4 NH) unit [25,26]. This simple calculation reproduces most of the band structure features obtained in more extensive calculations [27,28,29]. The seven energy bands are derived from the six Pz energy levels of benzene together with the Pz energy level of nitrogen.…”
Section: Spectroscopy and Photoexcitation Spectroscopymentioning
confidence: 88%